2020
DOI: 10.3389/fneur.2020.00166
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Ankle Control and Spasticity in Persons With Spinal Cord Injury: The Association Between Neurophysiologic Measures and Function. A Scoping Review

Abstract: Control of muscles about the ankle joint is an important component of locomotion and balance that is negatively impacted by spinal cord injury (SCI). Volitional control of the ankle dorsiflexors (DF) is impaired by damage to pathways descending from supraspinal centers. Concurrently, spasticity arising from disrupted organization of spinal reflex circuits, further erodes control. The association between neurophysiological changes (corticospinal and spinal) with volitional ankle control (VAC) and spasticity rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(131 reference statements)
1
2
0
Order By: Relevance
“…The significant positive training effects on behavioral accuracy of sequential ankle tracking and corresponding brain white matter integrity found in our study provide strong support for the applications of using sensor-based ankle tracking systems in the clinics, particularly for patients with neurological disorders, such as patients with stroke, spinal cord injury, or traumatic brain injury, who often present ankle control problems [ 69 – 76 ]. Training to improve ankle control of these patients is challenging in rehabilitation.…”
Section: Discussionsupporting
confidence: 58%
“…The significant positive training effects on behavioral accuracy of sequential ankle tracking and corresponding brain white matter integrity found in our study provide strong support for the applications of using sensor-based ankle tracking systems in the clinics, particularly for patients with neurological disorders, such as patients with stroke, spinal cord injury, or traumatic brain injury, who often present ankle control problems [ 69 – 76 ]. Training to improve ankle control of these patients is challenging in rehabilitation.…”
Section: Discussionsupporting
confidence: 58%
“…Increased corticospinal drive ( Schubert et al, 2008 ), earlier onset motor unit activation ( Van Cutsem et al, 1998 ), increased type II muscle fiber recruitment ( Wilson et al, 2012 ), and increased rate of force development ( Del Vecchio et al, 2019 ) are aspects of ballistic training that may support improved forward propulsion kinematics and facilitate walking speed modulation in persons with motor deficits. These features of training may account for the comparable changes in TLA we observed despite the marked differences in training mode and duration; however, the effects of the MST circuit in persons with MISCI may be restricted to the less impaired limb, where greater corticospinal tract preservation may contribute to enhanced ability to modulate lower limb kinematics ( Hope et al, 2020 ). Although evidence in non-injured adults suggests that even small-scale changes in TLA (i.e., Δ = 1.5°) can contribute to as much as 65% of the increase in propulsive force generated during slow to fast walking ( Hsiao et al, 2015 ), it is unclear whether the modest increase in TLA we observed was consequential to increases in walking speed among our participants.…”
Section: Discussionmentioning
confidence: 85%
“…One possibility is that it contributes to improved ankle control [16], thereby allowing for improved foot clearance. In the development of TSS interventions to improve functional outcomes, it is important to understand how it influences both voluntary and involuntary muscle activation and how it may contribute to the ability to achieve adequate dorsiflexion [23].…”
Section: Introductionmentioning
confidence: 99%